2022
DOI: 10.1177/00033197221121008
|View full text |Cite
|
Sign up to set email alerts
|

Remnant Cholesterol and the Risk of Coronary Artery Disease in Patients With Type 2 Diabetes

Abstract: Among statin-treated patients with type 2 diabetes mellitus (T2DM), there is still a great residual cardiovascular risk. Previous studies found that the level of remnant cholesterol (RC) could predict the coronary artery disease (CAD) risk. In the present study, we enrolled 4145 patients with T2DM; 2784 (67.2%) were male and their median age was 62 years. After multivariate logistic analyses, plasma RC level was significantly and independently associated with CAD [odds ratio (OR) 13.524, 95% confidence interva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Studies 10 have reported that high RC level is positively correlated with the occurrence and severity of retinopathy in patients with T2DM. Wang et al 25 also find that RC could increase the risk of cardiovascular disease, especially in patients with T2DM. Sheng et al 11 suggest that unconventional lipid parameters have higher diagnostic performance for future diabetes risk than conventional lipid parameters and both TG/HDL‐C and TC/HDL‐C are great indicators for predicting the occurrence of diabetes.…”
Section: Discussionmentioning
confidence: 95%
“…Studies 10 have reported that high RC level is positively correlated with the occurrence and severity of retinopathy in patients with T2DM. Wang et al 25 also find that RC could increase the risk of cardiovascular disease, especially in patients with T2DM. Sheng et al 11 suggest that unconventional lipid parameters have higher diagnostic performance for future diabetes risk than conventional lipid parameters and both TG/HDL‐C and TC/HDL‐C are great indicators for predicting the occurrence of diabetes.…”
Section: Discussionmentioning
confidence: 95%
“…In a study of 4145 patients with type 2 diabetes, after multivariate logistic analyses, the level of plasma remnant cholesterol was significantly and independently associated with CAD (OR: 13.524; 95% CI: 7.058–25.912; p < 0.001) after adjustment for conventional risk factors, such as age, gender, hypertension, and other lipid levels [ 95 ].…”
Section: Remnant Lipoproteinsmentioning
confidence: 99%